Corporate Governance and Earnings Quality in Chinese Information Technology Listed Companies - FENG, Shuo (2018)
This dissertation explores the relationship between corporate governance and earnings quality in Chinese information technology listed companies. Earnings management is selected among many proxies of earnings quality because of its popular using by researchers and available to obtain. Earnings management is proxied by abnormal accruals in this research and the principle is that the more abnormal accruals, the more earnings management and resulting in worse earnings quality. The variables used to represent corporate governance in our research are board size, the independence of board, the separation of chairman and CEO, the proportion of shareholdings held by executives, board meetings, the proportion of directors, supervisors and executives’ remuneration and the number of four main committees set up, which are chosen to examine their impacts on earnings quality. The data resource is from China Stock Market and Accounting Research (CSMAR) database and a panel data of 539 Chinese information technology listed companies from year 2012 to 2017 is chosen as sample, excluding companies with missing data and insignificant or not appropriate data which may affect our research results. In addition, three control variables which are firm size, return on asset and leverage ratio are also included in our research in order to represent other factors which also have effects on earnings quality but not belonging to the aspect of corporate governance. The research process includes the calculation of abnormal accruals, descriptive analysis, correlation analysis, the chosen of appropriate regression model and finally is the regression analysis. The research result is that the independence of board, the separation of chairman and CEO, and the proportion of shareholdings held by executives are significantly negative related to abnormal accruals, thus positively related to earnings quality in Chinese information technology listed companies. But the board size is significantly negative related to earnings quality. These results indicate that a company with the separation of duty of chairman and CEO will have higher earnings quality and also, the more independence of board, the better earnings quality. Moreover, the company should do efforts to improve the proportion of shareholdings held by executives, which will reduce the information and interest asymmetry, thus reducing earnings management and improving earnings quality. What’s more, the result between board size and earnings quality is negative suggests that an appropriate level of board size is important for a company because of the lower operating efficiency and lower return on asset features of large board size. Unfortunately, the other three independent variables are tested not significant in our sample and research, which may because of the limitations of the research. Keywords: corporate governance; abnormal accruals; earnings management; earnings quality